High prevalence of complementary and alternative medicine use among patients with sickle cell disease in a tertiary hospital in Lagos, South West, Nigeria - A. A. Busari; M. A. Mufutau (BMC, 2017)
Abstract Background Attention and interest in the use of complementary and alternative medicine (CAM) has been reignited globally, most especially in patients with chronic diseases. Sickle cell disease (SCD) is one of such chronic diseases associated with devastating clinical and psychosocial consequences, thus leading those affected to seek alternative treatment apart from orthodox medicine. Hence, this study aimed to determine the prevalence, pattern and tolerability of the use of CAM in patients with SCD in the Lagos University Teaching Hospital (LUTH). Methods This was a cross-sectional survey of 200 respondents with SCD attending the hematology clinics of the Lagos University Teaching Hospital over a period of 3 months. Data on socio-demographic characteristic, clinical profile, the types and sources of CAM used were collected using a well structured pretested questionnaire. The data obtained were analyzed using Statistical Package for Social Sciences (SPSS®) version 17. Result Of the 200 patients who participated in the study, 113; 56.5% were males and 87; 43.5% were females. Majority of the SCD patients were 1-10 years old and their mean age was 18.8 ± 14.39 years. CAM was reportedly used by 88.5% of the respondents. Biological (herbal) products 156; 62.9% were the most commonly used CAM, followed by alternative medical systems 52; 20.9% and mind-body interventions 30; 12.1%. Relations, friends and neighbors influenced 85.2% of CAM users by recommending CAM to them. Tolerability of CAM was perceived to be excellent as only 33 (18.6%) of the respondents abandoned the use of CAM. Comparing CAM users and CAM non-users, there was no statistical significant difference in the proportion of those >18 years (45.76% vs 52.17%; p = 0.658), those who experienced two or more crises (51.41% vs 34.78%; p = 0.183), and those with stable haemoglobin concentration of >7 g/dL (15.81% vs 8.69%; p = 0.539) More patients among CAM non-users (91.30%) significantly spend over 3000 Naira (USD 15) per month on medicine than CAM users (4.51%) (p < 0.001). Conclusion CAM use is highly prevalent among adults with sickle cell diseases in Nigeria. CAM is well tolerated and relatively affordable by these patients. Clinician awareness and understanding of the factors influencing the use of CAM and the potential herbal-orthodox medicine interaction are crucial during hospital treatment of these patients.